The Changing Character of the American Right, Volume I
XXII, 336 p. 49 illus., 26 illus. in color.
Keywords: These volumes analyze the transformation of the American right in recent years. While the roots of that transformation can be traced back to the 1970s, the last decade has seen further radical revisions of its ideology, style and policies. The contributors argue that both the organized Republican Party and the wider American right have changed profoundly, especially since the Trump presidency of 2017-2021, reflecting long- and short-term alterations to the political dynamics of the United States. These changes have major consequences for the country’s governance, for its social cohesion and for its constitutional order. Focusing on a range of topics including values and beliefs, partisanship and voting behaviour, race, religion and violence as well as on institutions and policies, these volumes brings together a distinguished team of scholars at a challenging time for the future of American democracy. Joel D. Aberbach is Distinguished Professor Emeritus of Political Science and Public Policy at the University of California, Los Angeles. His publications include Understanding Contemporary American Conservatism (2017) and (with Bert A. Rockman) In the Web of Politics: Three Decades of the U.S. Federal Executive (2000). Bruce E. Cain is Professor of Political Science at Stanford University and Director of the Bill Lane Center for the American West. His publications include Democracy More or Less: America’s Political Reform Quandary (2015) and (co-edited with Jon Herbert, Gillian Peele and Andrew Wroe) Developments in American Politics 9 (2022). Desmond King is Andrew W. Mellon Professor of American Government at Nuffield College, Oxford. His publications include Separate and Unequal: African Americans and the Federal Government (2007) and (with Rogers M. Smith) Still a House Divided: Race and Politics in the Obama Era (2013). Gillian Peele is Emeritus Fellow, Lady Margaret Hall, Oxford and Emeritus Associate Professor of Politics at University of Oxford. Her publications include Revival and Reaction: The Right in Contemporary America (1984), and (edited with Joel D. Aberbach) Crisis of Conservatism: the Republican Party, The Conservative Movement and American Politics after Bush (2011).